Investigation of The Antecedents of The Digital Mindset and Its Influence on Employee Intention to Stay in Generation Z: Empirical Study in The Indonesian Creative Industry - Luissa, Birgitta Annabel; Jimmy, So Yohanes; Tjahjana, David (The South East Asian Journal of Management, 2024)
Research Aims: This research aims to investigate the influence of a digital mindset on Generation Z employees’ intention to stay. Design/Methodology/Approach: This research was conducted using a quantitative approach involving 180 Generation Z employees in the creative industries. Data were analysed using Structural Equation Modelling with the SmartPLS tool. Research Findings: The research results show that the digital mindset of Generation Z employees has a positive effect on employee intention to stay. By having a strong digital mindset, employees tend to feel more supported by the organisation when facing technological changes and a rapidly developing learning culture. Digital flexibility and support between colleagues are the main influencing factors. The practical implication is that organisations can increase employee retention and maximise the potential of a digital technology-savvy workforce in the dynamic landscape of the creative industries. Theoretical Contribution/Originality: This research contributes by establishing a digital mindset as a new antecedent for employee intention to stay. Managerial Implications in the South East Asian Context: Digital mindset has been shown to be effective in addressing crises in organisational management. Management that applies this concept is able to sustain the organisation and its competitiveness over time. Research Limitations & Implications: To broaden the scope and gain more holistic insights, future research should consider involving other industries that may have connections or relevance to the aspects being researched. Additionally, comparing industries with varying levels of technological advancement could provide more comprehensive insights.